El proceso de atención al cliente y efectos de su imagen corporativa del almacén construhogar cía. Ltda. De la ciudad de Riobamba período 2013. - Padilla Usca, Fernanda Gabriela (2016)
The research aims to determine how the customer has an effect on the corporate image of the company, its content is the result of problematic analysis of the current situation specifically store ConstruHogar Cia. Ltda. In the city of Riobamba 2013 period. In relation to the methodological aspects deductive hypothetical method was applied, the research was: exploratory and descriptive, to collect information surveys and interviews were applied, with the results tables, charts, analysis and interpretation of the results were made, finally research indicated that the company ConstruHogar Cia. Ltda. were not encouraging, came to the conclusion that the performance of employees do not meet the quality standards required to have the desired corporate image, so it was necessary to consider a proposal sustentándose in the theoretical Corporate Branding Capriotti proposed by Peri.